2022
DOI: 10.3389/fgeed.2022.930110
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro genome editing to explore GNE functions

Abstract: GNE myopathy is an adult onset neuromuscular disorder characterized by slowly progressive distal and proximal muscle weakness, caused by missense recessive mutations in the GNE gene. Although the encoded bifunctional enzyme is well known as the limiting factor in the biosynthesis of sialic acid, no clear mechanisms have been recognized to account for the muscle atrophic pathology, and novel functions for GNE have been hypothesized. Two major issues impair studies on this protein. First, the expression of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
1
8
1
Order By: Relevance
“…In the present study, we established a Gne -knockout cell model, using the murine myoblast cell line C2C12 to study the efficiency of exogenous ManNAc and sialic acid (Neu5Ac) administration in a skeletal muscular background. First, we found that the absence of GNE prevents the differentiation of myoblasts into mature myotubes, as described previously in other studies ( Ilouz et al. 2022 ; Schmitt et al.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, we established a Gne -knockout cell model, using the murine myoblast cell line C2C12 to study the efficiency of exogenous ManNAc and sialic acid (Neu5Ac) administration in a skeletal muscular background. First, we found that the absence of GNE prevents the differentiation of myoblasts into mature myotubes, as described previously in other studies ( Ilouz et al. 2022 ; Schmitt et al.…”
Section: Introductionsupporting
confidence: 88%
“…HEK-293 (ACC 305) and C2C12 cells (ACC 565) were purchased from DSMZ (Braunschweig, Germany). Sol8 wild type and Sol8 Gne -knockout cells were kindly provided by Stella Mitrani-Rosenbaum (Hadassah–The Hebrew University Medical Center, Israel) ( Ilouz et al. 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRAT1 is known to be involved in the cellular response to DNA damage (Ertl et al, 2021). This result is particularly interesting since in a muscle cellular model knocked out for GNE that has been recently established in our laboratory, we also see this DNA damage/repair pathway affected (Ilouz et al, 2022). The human orthologue of si: ch211-198k9.6, is RBBP6 (retinoblastoma tumor suppressor 6binding protein), known to be involved in mRNA processing, cell cycle regulation, and ubiquitination activity (Xiao et al, 2019).…”
Section: Discussionmentioning
confidence: 82%
“…However, there is currently no commercialized pharmacological intervention available to reduce brain Neu5Ac in animal models. There are gene‐editing animal models targeting endogenous Neu5Ac production being developed recently 77–79 . In some of these models, brain Neu5Ac decreases to varying extents and impaired motor function could be observed 77,80 .…”
Section: Discussionmentioning
confidence: 99%